2013
DOI: 10.1111/nmo.12170
|View full text |Cite
|
Sign up to set email alerts
|

Low‐resolution colonic manometry leads to a gross misinterpretation of the frequency and polarity of propagating sequences: Initial results from fiber‐optic high‐resolution manometry studies

P. G. Dinning,
L. Wiklendt,
I. Gibbins
et al.

Abstract: Doubling the sensor spacing from 1 to 2 cm nearly halves the number of PSs detected. Tripling the sensor spacing from 1 to 3 cm resulted in a 30% chance of incorrectly labeling PSs. Closely spaced pressure recording sites (<2 cm) are mandatory to avoid gross misrepresentation of the frequency, morphology, and directionality of colonic propagating sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
115
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(120 citation statements)
references
References 32 publications
2
115
2
1
Order By: Relevance
“…Overall, these studies have demonstrated that the colonic response to a meal (i.e. the number of retrograde propagating sequences and the number of high-amplitude propagating sequences) is reduced in adults with functional constipation as compared to healthy subjects (Dinning et al, 2013). In adults with functional diarrhea, the number of high and low amplitude anterograde propagating sequences was increased, while simultaneous and retrograde activity was less frequent (Herbst et al, 1997).…”
Section: Invasive Methodologiesmentioning
confidence: 86%
See 3 more Smart Citations
“…Overall, these studies have demonstrated that the colonic response to a meal (i.e. the number of retrograde propagating sequences and the number of high-amplitude propagating sequences) is reduced in adults with functional constipation as compared to healthy subjects (Dinning et al, 2013). In adults with functional diarrhea, the number of high and low amplitude anterograde propagating sequences was increased, while simultaneous and retrograde activity was less frequent (Herbst et al, 1997).…”
Section: Invasive Methodologiesmentioning
confidence: 86%
“…As reported by Dinning and colleagues, the study of colonic motility was performed with catheters applying different recording systems (water-perfused or solid state) but generally allowing to measure the pressure created by colonic contractions on a limited number of pressure sensors (from 4 to 16) spaced 7-12 cm one from each other (conventional or low-resolution manometry) (Dinning et al, 2013). Manometric recordings of the relatively inaccessible human colon are complicated by a number of technical difficulties that typically necessitate partial or total removal of colonic contents in order to position a recording catheter.…”
Section: Invasive Methodologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of the fiberoptic data was performed using software (that we called "PlotHRM") developed by one of the authors (L. Wiklendt). PlotHRM was written in Matlab (MathWorks, Natick, MA) and Java (Sun Microsystems, Santa Clara, CA) (11,19).…”
Section: Recording Methodsmentioning
confidence: 99%